Metafora Konseptual dalam Slang Fandom K-Pop di Platform X Pada akun @starfess: Sebuah Kajian Linguistik Kognitif - Suci Pratiwi; Febrian Nasution (Penerbit Jurnal Indonesia, 2026)
This research study examines metaphor usage in fan posts from @starfess within the K-Pop community discourse. Adopting a cognitive linguistics framework, this research utilizes a qualitative descriptive methodology with data collected from September 1 to October 31, 2025. The analytical phase encompasses the identification and classification of conceptual metaphors based on Lakoff and Johnson's (1980) framework, subsequently employing conceptual mapping to elucidate complicated words. The analysis revealed several forms of vernacular metaphors across three categories: structural metaphors including 'comeback' and 'solo debut'; orientational metaphors comprising 'top tier visual' and 'flop'; and ontological metaphors such as 'hiatus' and 'bias.' Findings indicate that K-Pop community slang transcends its role as a mere communicative device, instead reflecting the community's cognitive patterns, value systems, and social structures. Within this community, metaphors operate as cognitive tools that furnish an organized conceptual framework for navigating the entertainment ecosystem. This study aims to contribute to the field of cognitive linguistics in popular culture studies.